A metagenomic approach to characterize temperate bacteriophage populations from Cystic Fibrosis and non-Cystic Fibrosis bronchiectasis patients - Tariq, Mohammad A.; Everest, Francesca L. C.; Cowley, Lauren A.; De Soyza, Anthony; Holt, Giles S.; Bridge, Simon H.; Perry, Audrey; Perry, John D.; Bourke, Stephen J.; Cummings, Stephen P.; Lanyon, Clare V.; Barr, Jeremy J.; et al. (Frontiers in Microbiology, 2015)
Pseudomonas aeruginosa (Pa), normally a soil commensal, is an important opportunistic pathogen in Cystic Fibrosis (CF) and non-Cystic Fibrosis Bronchiectasis (nCFBR). Persistent infection correlates with accelerated decline in lung function and early mortality. The horizontal transfer of DNA by temperate bacteriophages can add gene function and selective advantages to their bacterial host within the constrained environment of the lower lung. In this study, we chemically induce temperate bacteriophages from clonal cultures of Pa and identify their mixed viral communities employing metagenomic approaches. We compared 92 temperate phage metagenomes stratified from these clinical backgrounds (47 CF and 45 nCFBR Pa isolates) using MG-RAST and GeneWise2. KEGG analysis shows the complexity of temperate phage accessory gene carriage increases with duration and severity of the disease. Furthermore we identify the presence of Ig-like motifs within phage structural genes linked to bacterial adhesion and carbohydrate binding including Big_2, He_Pig and Fn3. This study provides the first clinical support to the proposed bacteriophage adherence to mucus (BAM) model and the evolution of phages interacting at these mucosal surfaces over time.